Structural Stone Surfaces: New Compression Shells Inspired by the Past. (September 2015) - Block, Philippe; Van Mele, Tom; Rippmann, Matthias; Menges, Achim
<x xml:space="preserve">Abstract</x> Much of our architectural heritage today is built out of unreinforced masonry. It is often unclear why historic masonry structures still stand when conventional analysis tools have predicted their failure. In order to ensure the safety of these existing structures, there is an acute need for innovative tools that can accurately analyse their stability. Associate Professor Philippe Block, Tom Van Mele and Matthias Rippmann of the Block Research Group, part of the Institute of Technology in Architecture at ETH Zurich demonstrate how computational form‐finding methods and design tools for masonry structures that stand in pure compression, such as arches and vaults, make it possible to design expressive and efficient surface structures that can be built with very little or low‐quality material. By studying the techniques of medieval master builders, the Block Research Group has also developed new ways of building with masonry, enhanced by current construction and fabrication technologies. These new tools and reinvented construction methods can be applied in different contexts: for instance, by studying the structure of Gothic cathedrals, they manage to dramatically reduce the use of materials in office construction.